Use Adaptive Hysteresis Band to Unified Power Quality Conditioner Control for Voltage and Current Disturbances Treatment - مقدسي كارلو; حسامو عصام; قنجرواي حسن (Latakia University Journal -Engineering Sciences Series, 2021)
The use of sensitive electronic devices has increased in recent years, and the power quality has become an important requirement in electrical power systems, as network disturbances (harmonics, swell voltage, voltage drop, etc.) affect consumers and lead to technical-economic damage. One of the most prominent solutions to address power quality problems is the Unified Power Quality Conditioner (UPQC). In this paper, we study the unified power quality conditioner used to improve the power quality in distribution networks where Park conversions will be used to obtain the required reference signals, and we also used an adaptive hysteresis band to generate electronic keys pulses in both the serial and shunt converter, where the hysteresis band width determined depending on fuzzy logic. The validity of the studied system was validated by simulating different disturbances and comparing the results with the Sinusoidal Pulse width modulation (SPWM) was used to control the two converters. The results showed an improvement in the power quality through the use of the adaptive hysteresis band controller, and this appeared by reducing the total harmonic distortion factor (THD%), which resulted in improving the wave of both the voltage and current wave.